Single-cell analysis of diverse immune phenotypes in malignant pleural effusion - Zhong-Yin Huang (Nature Portfolio, 2021)
Detailed immune cell subset identification in human lung (malignant pleural effusion) MPE is important for diagnosis and prognosis. Here the authors use single cell RNA sequencing to identify immune cell types within MPE and show differential gene expression compared to circulating immune cells in blood.